DEVELOPING STRATEGY OF MAINTENANCE, REPAIR AND OVERHAUL OF WARSHIPS IN SUPPORT OF NAVY OPERATIONS READINESS - Abdul Rahman; Andry Kuswoyo; Ayip Rivai Prabowo; Okol Sri Suharyo (JOURNAL ASRO, 2020)
Maintenance, Repair, and Overhaul is an action to control, know and ensure the life of a defense equipment. Indonesia should have a concept for maintenance, repair and overhaul in the defense industry. The problem in this research is how to determine priority weighting and development strategy plan for Maintenance, Repair and Overhaul warships implemented by Fasharkan Surabaya to support the readiness of marine operations. The purpose of this study is making a strategic plan for the development of Maintenance, Repair and Overhaul warships carried out by Fasharkan Surabaya in support of marine operations readiness. The method used in this study is the determination of criteria by hierarchy using the Analytical Hierarchy Process (AHP). The results of the study show that Strategic priorities using the AHP concept obtained 5 strategies, namely 1) Cooperation in Higher Education related to technology with the highest weight, 0.42. 2) Improving the quality of Human Resources with a weight of 0.23. 3) Improve Education and Training with a weight of 0.18. 4) Fulfillment of Human Resources according to the List of Personnel Arrangement with a weight of 0.11. 5) Cooperation with the defense industry with a weight of 0.06.Keywords: Maintenance, Repair and Overhaul, Warships, AHP, Marine Operation Readiness.